2011
DOI: 10.1177/1474022211426906
|View full text |Cite
|
Sign up to set email alerts
|

Creating socially networked knowledge through interdisciplinary collaboration

Abstract: We report on the experience of creating a socially networked system, the Research-oriented Social Environment (RoSE), for representing knowledge in the form of relationships between people, documents, and groups. Developed as an intercampus, interdisciplinary project of the University of California, this work reflects on a collaboration between scholars in the humanities, software engineering, and information studies by providing an opportunity not only to synthesize different disciplinary perspectives, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This perspective is reinforced through graduate training where students are trained to be solitary scholars and are not generally seen as collaborators and equal contributors when working as research assistants [12,14,31]. Despite this context, several examples of humanists collaborating with each other and those in the disciplines exist [5,22,29,[32][33][34]. However, this context raises questions about the nature of collaboration in a humanities research project.…”
Section: Contextmentioning
confidence: 99%
“…This perspective is reinforced through graduate training where students are trained to be solitary scholars and are not generally seen as collaborators and equal contributors when working as research assistants [12,14,31]. Despite this context, several examples of humanists collaborating with each other and those in the disciplines exist [5,22,29,[32][33][34]. However, this context raises questions about the nature of collaboration in a humanities research project.…”
Section: Contextmentioning
confidence: 99%
“…(An example is the shared-tags component of the Collex environment for searching distributed digital resources.) 12 And theoretically, new media theorists such as Galloway and Thacker (2007) are adapting social-network theory to explore ‘a theory of networks’; literary scholars such as Piper (2009), Moretti (2011), and Z. Frank (2011) use social-network theory to model literature; and the Transliteracies Project (n.d.) that I direct has developed a project that exploits the idea of social networks for the historical study of the humanities (in the RoSE (n.d.) Research-oriented Social Environment about which some of my collaborators write in this issue of Arts and Humanities in Higher Education (Chuk et al, 2012)).…”
Section: A Report On the State Of The Digital Humanitiesmentioning
confidence: 99%
“…That is, most publishing, data analysis, and grant writing in the humanities is still single or dual authored (Lariviere, Gingras, & Archambault, 2006). Although there has been much optimism about how the collaborative model could be applied to the humanities to increase information flow, copublishing, and innovation, few studies have actually observed the extent to which such networks are successful in practice (Chuk, Hoetzlein, Kim, & Panko, 2012; McGrath, 2011). Yet scholars in the humanities are becoming more aware of the relevance of networking and the use of boundary-spanning teams to stimulate creativity, address novel research questions, and tackle complex problems.…”
Section: Introductionmentioning
confidence: 99%